Palaeophytogeographical contributions to the Iberian vegetal landscape interpretation: state of the art and new prospects for research - Alcalde, C.; García-Amorena, I.; García Álvarez, S.; García Calvo, D.; García García, R.; Génova, M.; Gil Borrell, P.; Gómez Manzaneque, F.; Maldonado, J.; Morla, C.; del Nido, J.; Postigo, J. M.; et al. (Forest Systems, 2006)
The palaeobotanical studies that have been accomplished in the Iberian Peninsula during the last two decades have provided a great amount of data that can be applied in geobotanical knowledge. In most of the cases, those results have contributed to solve classical scientific debates regarding vegetal landscapes interpretations. One of the most relevant discussions is related to the aloctonous or non-aloctonous origin of much of the Iberian pine forests, on diverse Iberian habitats. The main contributions of Palaeobotany to the processes that explain the present distribution of plants are reviewed in a spatial and temporal framework, from old geological periods (Mesozoic, Tertiary) to the recent ones (Pleistocene, Holocene). Linked to the history of our vegetal landscapes, Pleistocene and Holocene epochs have been treated from two different points of view: firstly the problems within extensive territorial environments and, secondly, the problems related to the interpretation of the evolution and/or behaviour of taxa. In the last part, some new investigation trends related to palaeophytogeography are exposed, focusing on the high potential interest on being applied to Iberian ecosystems.